The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Num Pages: 25-40
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Review of Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference. - Lindner, Katharina (Transnational Cinemas, 2015)
On the 'Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference', held at the University of Hamburg, 14-15 October 2014, alongside the Hamburg International Queer Film Festival.
Num Pages: 97-103
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Lesbian Cinema after Queer Theory - Bradbury-Rance, Clara (Edinburgh University Press, 2019)
The unprecedented increase in lesbian representation over the past two decades has, paradoxically, coincided with queer theory’s radical transformation of the study of sexuality. In Lesbian Cinema after Queer Theory, Clara Bradbury-Rance argues that this contradictory context has yielded new kinds of cinematic language through which to give desire visual form. By offering close readings of key contemporary films such as Blue Is the Warmest Colour, Water Lilies and Carol alongside a broader filmography encompassing over 300 other films released between 1927 and 2018, the book provokes new ways of understanding a changing field of representation. Bradbury-Rance resists charting a narrative of representational progress or shoring up the lesbian’s categorisation in the newly available terms of the visible. Instead, she argues for a feminist framework that can understand lesbianism’s queerness. Drawing on a provocative theoretical and visual corpus, Lesbian Cinema after Queer Theory reveals the conditions of lesbian legibility in the twenty-first century.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Europe (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé